1983
DOI: 10.1093/ajcn/38.6.860
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary fat on blood pressure in a rural Finnish population

Abstract: Thirty couples living in Liperi, a community of North Karelia, aged 40 to 50 yr participated in a dietary intervention study to assess the influence of dietary fat on blood pressure and other parameters. After a weeklong base-line period the subjects consumed a low fat diet (24% of energy) with a polyunsaturated/saturated fat ratio (P/S) of 1.2 for 6 wk. After this 6-wk intervention period the subjects resumed their normal diets (36% energy from fat, P/S 0.15) for an additional 6-wk period. Body weight remaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…The HP diet of the present study was closely similar to the intervention diet of the 1980 study. 24,50 The main difference between the two studies is found in the background diets of the subjects constituting the baseline against which the results of the interventions were compared. In 1980 the subjects habitually consumed a diet with 39 en% fat and 3.2 en%, PUFA.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The HP diet of the present study was closely similar to the intervention diet of the 1980 study. 24,50 The main difference between the two studies is found in the background diets of the subjects constituting the baseline against which the results of the interventions were compared. In 1980 the subjects habitually consumed a diet with 39 en% fat and 3.2 en%, PUFA.…”
Section: Discussionmentioning
confidence: 99%
“…24,25,29 We excluded hypertensive individuals and those with low BP levels unless the spouse fulfilled the criteria for recruitment. At screening a large proportion of the participants were borderline hypertensive, but both SBP and DBP levels showed a tendency to decline after screening and during the baseline period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations